Dampak Penggunaan Serious Game “ECOGO” Terhadap Hasil Belajar Pemilahan Sampah Menggunakan Metode Kuasi-Eksperimen - Diny Anggriani Adnas; Melisa Melisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Education on waste sorting is an important foundation in sustainable environmental management, but the use of conventional learning media still has limitations in attracting student interest and engagement. With the development of digital learning technology, serious games have the potential to become an alternative, more interactive and effective educational media. This study aims to evaluate the effectiveness of the serious game ECOGO on student learning outcomes and analyze the game's playing experience and usability level. The study involved 30 students of Meitrya Junior High School, Batam (aged 12–14 years) with a quasi-experimental one-group pretest–posttest design. Data were collected using a knowledge test, a Likert-scale usability questionnaire (0–4), and the Game Experience Questionnaire (GEQ) core module, then analyzed using a paired sample t-test and descriptive analysis. The results showed a statistically significant increase in learning outcomes between the pre-test and post-test scores (p < 0.001). The usability evaluation showed an average score of 2.94 on a scale of 4, indicating a high level of ease of use and user acceptance. The GEQ results confirmed a very positive gaming experience with high average scores on Positive Affect (3.27), Flow (2.99), and Competence (3.21), and low scores on Negative Affect and Tension (≈0.67). These findings indicate that a positive and immersive gaming experience contributes to improved student learning outcomes, thus ECOGO is considered effective as an interactive learning medium based on serious games in junior high school education.